PENGUKURAN KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA WISATA AGRO MUMBUL GARDEN PTPN. XII KEBUN MUMBUL JEMBER - Laili Rahmawati; Dra. Sri Wahyuni (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
This research is use descriptive with the quantitative approach. Research objectives is measure performance tourism agro mumbul garden with the methods balanced scorecard. Performance measurement includes the financial perspective measured by the ratio growth and the ratio profitability and perspective customers measured by the acquisition customers and customer satisfaction. A source of the data used was primary data and data skunder. Technique the sample collection use accidential sampling namely taking with the sample certain first designed meeting. Sample used in this research as many as 50 respondents. The results of the analysis data indicate that the company performance tourism agro mumbul garden in terms of financial perspective measured by the ratio growth good enough because of the increase in profit from sales. Financial perspective measured by the ratio profitability good enough .The company performance in terms perspective customers measured by the acquisition customers bad because a decline in the percentage acquisition customers from the previous year. Perspective customers measured by customer satisfaction which includes; the product, price, promotion, place or the location, an employee ( people ), process , and physical evidence of on the criteria quite good because the majority of respondents felt quite satisfied with services offered by tourism agro mumbul garden.